Analysis of the Fluid Cavitation Effect of Friction Pair on Double Arc Groove Hydro-viscous Drive - Ren Zhong; Zhang Hong; Liu Qiuzu (Jixie chuandong)
Taking the double arc groove hydro-viscous drive which uses fiction plate as the research object,the Fluent fluid analysis software is used to calculate the fluid cavitation effect of friction pair,the influence of rotation speed and fluid viscosity on cavitation zone is analyzed,as well as before and after oil film bearing capacity changes,the results show that the shape of cavitation zone is like vertical long strip,the cavitation starts from the outside radius direction,and becomes more significant along the radius increasing direction. Decreasing rotation speed or viscosity can slow down cavitation speed effectively. The deeper and more grooves,the smaller the gas bearing ratio,when the groove depth is more than 0. 3 mm and the groove number is more than 45 are determined as the best. The cavitation effect influences the performance of friction pairs,and decreases the oil bearing capacity,the effect of cavitation on the oil film bearing capacity will be more significant with the increase of groove depth and decrease of groove numbers.